Aspectos morfológicos e moleculares do desenvolvimento cerebral casta-específico em Apis mellifera - Paula Junior, Delcio Eustaquio De (2019)
Apis mellifera are insects known for their eusociality. The adults in the species; drones, queens and workers, display a clear division of labor and generation overlap. Queen and workers are a classic example of diphenism, which is determined by the differential feeding, royal jelly or worker jelly received between the third and fifth instar larvae. Feeding influences the brain development in many species, including in the A. mellifera, which shows differential brain morphogenesis between queens and workers. During the larval stage, the queens’ brain are larger, with a higher number of neuroblasts and also with a higher rate of cell proliferation. However, it is known that the adult brain in workers is proportionally larger; therefore, the hypothesis is that an inversion of brain size happens during the pupal and/or pharate-adult development through the action of hormonally modulated genes. By means of oligonucleotide microarrays, a set of genes differentially expressed in queens and worker Pp brain were identified, among which may be primordial genes for caste specific brain development. Thus, the objective was to determine the morphological dynamics and molecular bases of brain development during the pupal and pharate-adult period in workers and queens. The results showed that workers’ brains develop more than queens’ brains in the pupal and pharate-adult period. The mushroom body and peduncular body occupy a larger area in the workers’ brain and there is anatomical lateralization related to these structures in the brain of both castes. Searching for molecular determiners in the brain morphogenesis, it was analyzed the expression of 17 transcripts, tum, mnb, ATPsynβ, ant, InR-1, InR-2, ILP-1, ILP-2, Tor, hex 70a, hex70b, hex 110, lncov-1, LOC 726407, caspase-1, EcR-A and EcR-B, and it was verified that only hex 110 is not differentially expressed among the castes. It was analyzed the answer from 8 of them (tum, mnb, ATPsynβ, ant, ILP-1, ILP-2, lncov1e caspase-1) to the hormones HJ e 20E. They all answer to at least one of the hormones. Besides, it was immunolocated the protein products from the genes ATPsynβ and hex 70a and observed that the first one presents a cytoplasmic localization and the second one a cytoplasmic and nuclear localization. Altogether, the results make us believe that the hormonal environment, more specifically, the high tittles of ecdysteroids, is differently interpreted at the queens’ and workers’ brain, which creates differences in the gene expression patterns that favors the brain development in worker bees. RNAi assays are underway and will look at the effects of post-transcriptional silencing of mnb, a gene that appears to play a key role in the differential brain morphogenesis process in A. mellifera during the pupal and pharate-adult periods.